Pemanfaatan Artificial Intelligence (AI) sebagai Asisten Literasi Akademik dalam Pembelajaran Bahasa Indonesia di Perguruan Tinggi - Abdulloh Abdulloh; Sudarmaji Sudarmaji; Salamah Salamah (STKIP PGRI Bandar Lampung, 2025)
The development of digital technology has influenced learning practices in higher education, including Indonesian language instruction. One emerging innovation is the use of Artificial Intelligence (AI) as an academic literacy assistant. This study aims to describe the use of AI in Indonesian language learning at the university level and examine its role in supporting students’ academic literacy. This research uses a descriptive qualitative approach involving students and Indonesian language lecturers. Data were collected through interviews, questionnaires, classroom observations, and analysis of students’ academic writing. The results show that AI helps students organize writing structures, improve linguistic accuracy, and increase confidence and learning autonomy. The integration of AI also enhances students’ interest and engagement in academic literacy activities. However, lecturer guidance and reinforcement of academic ethics are essential to prevent overreliance on AI. These findings indicate that AI can function effectively as an academic literacy assistant when integrated pedagogically and responsibly in higher education.